The impact of water level changing in the Franciscan heritage located in coastal areas and river banks in Portugal: perspectives and challenges - Genin, Soraya M.; Volzone, R. (Religious Heritage: Celebrating and conserving places of religious and ritual significance in a global world and in changing climates, 2022)
Climate change is worldwide one of the greatest environmental challenges. There is a clear need to improve climate adaption, in order to minimize the risks to communities, the environment and the cultural heritage. However, this issue is not always a priority and is not taken into consideration in some municipal or regional urban planning. Within the European Union’s Horizon 2020 JPICH project “F-ATLAS. Franciscan Landscapes: the Observance between Italy, Portugal and Spain” and the International Day of Monuments and Sites 2022, an academic research on the theme “Heritage and Clima” has been developed in the curricular unity “Conservation and Sustainability” at ISCTE-IUL, involving young future architects in this issue. Former convents of the Saint Francis order, located in Portuguese coastal areas and river banks, have been identified. Data have been collected about the history of the convents, and a preliminary analysis of the state of conservation has been carried out. When possible, on-site surveys have been developed. Collected data have been crossed with the water level projection for the next three decades, in order to define a critical map of theses religious heritage at risk. Local administrations have been contacted to understand if they are aware of the problem and have an inventory of the heritage at risk and which plans are being implemented to predict and assess the impacts of climate change on the cultural heritage. Findings can promote awareness by public administrations and local communities, leading to the definition of protection, conservation and management strategies for cultural heritage, towards a sustainable local development.